Sifat Fisiokimia dan Aroma Ekstrak Vanili - Dwi Setyaningsih; Meika Syahbana Rusli; Nurmalia Muliati (Jurnal Ilmu Pertanian Indonesia, 2007)
The curing process of vanilla beans from dried vanilla to vanilla extract would give added value to vanilla products. Aroma and taste in vanilla extract depend on variety of plants, cultivation methods, and curing process. Indonesian vanilla extract tend to give woody and phenolic aroma because it was harvested too early and it did not cure perfectly. This study was to identify the physicochemical and aroma characteristics of vanilla extracts from importer, exporter, and vanilla extracts from the newest experiment from our laboratory. There  were seven samples, three from importers (Tahiti grade I, Tahiti grade II, Virginia Dare), two from Indonesian Vanilla exporters (Djasula Wangi, Cobra), and two from our laboratory (G11, 57). The  physicochemical characteristics which were analyzed were vanillin content, ash, soluble ash, alkalinity of soluble ash, alkalinity of  total ash, total acidity, and lead number, all compared with the Food and Drugs Administration (FDA) standard. Sensory analysis used aroma description test consist of qualitative descriptive test (in-depth interview and focus group methods) and quantitative descriptive analysis. The result showed that the laboratory's sample from modified curing process (G11) followed the FDA standard in physicochemical characters, but the aroma description was not as strong as the aroma of vanilla extract from exporters, namely Cobra with creamy, sweet, and vanilla aroma; and vanilla extract from importer, namely Virginia with smoky and spicy aroma.   Keywords: vanilla extracts, aroma